Analisis Prinsip-Prinsip Esensial Dalam Meningkatkan Motivasi Siswa Melalui Pendekatan Berdasarkan Konsep Rothwal - Qurniati, Alif; Alfisyahrani, Aura; Cahyani, Ilhimimah; Savitri, Malinda Dewi; Sutarto, Sutarto (Peneliti.net, 2024)
Principles are the basis for learning efforts, are the most important model for achieving satisfactory results for both students and teachers, and are the most important model for achieving satisfactory results for both students and teachers, and are desired so that the learning process can be successful. Learning is the process of changing behavior from someone we don't know to someone we know. Defining the principle of self-directed learning: creating and producing respectful and enjoyable study and learning activities. As a basis, you need to know learning principles and theories. These principles are used by both students and teachers as a basis for learning efforts to achieve the desired goals . Motivation begins with the word